All-cause and cause-specific mortality in rheumatoid arthritis are not greater than expected when treated with tumour necrosis factor antagonists. Issue 7 (26th February 2007) - Carmona, Loreto; Descalzo, Miguel Ángel; Perez-Pampin, Eva; Ruiz-Montesinos, Dolores; Erra, Alba; Cobo, Tatiana; Gómez-Reino, Juan J
Abstract : Background: Mortality is increased in rheumatoid arthritis (RA), mainly because of cardiovascular (CV) events, cancer and infections. Recent data suggest that treatment with tumour necrosis factor (TNF) antagonists may affect this trend. Objective: To assess whether treatment with TNF antagonists is associated with reduction in CV events, cancer and infection rates, and in mortality in patients with RA treated and not treated with TNF antagonists. Methods: BIOBADASER is a registry for active long-term follow-up of safety of biological treatments in patients with RA. It includes 4459 patients with RA treated with TNF antagonists. EMECAR is an external RA cohort (n = 789) established to define the characteristics of the disease in Spain and to assess comorbidity. The incidence density (ischaemic heart disease) of CV events, cancer and infections was estimated and compared. The standardised mortality ratio was compared with the rate in the general population. A propensity score was used to match cohorts by the probability of being treated. Results: Rates of CV and cancer events are significantly higher in EMECAR than in BIOBADASER (RR 5–7 for different CV events, and RR 2.9 for cancer), whereas the rate of serious infections is significantly higher in BIOBADASER (RR 1.6). Mortality ratio of BIOBADASER by EMECAR is 0.32 (0.20–0.53) for all causes of death, 0.58 (0.24–1.41) for CV events, 0.52 (0.21–1.29) for infection and 0.36 (0.10–1.30) for cancer-related deaths. Conclusion: Morbidity, other than infection, and mortality are not higher than expected in patients with RA treated with TNF antagonists.